Talking about the 'rotten fruits' of Rio 2016: Framing mega-event legacies. (February 2021) - Talbot, Adam
Legacy has become a watchword of hosting mega-events in recent years, used to justify massive spending and far-reaching urban transformations. However, academic studies of legacy outcomes suggest there is only limited evidence for the efficacy of using mega-events to deliver broader policy goals. The discourse of legacy promulgated by the International Olympic Committee promotes a fantastical vision of the possibilities created by mega-events while obfuscating critical analyses of legacy. This paper explores legacy talk among a wholly different group – activists who have protested against the Olympic Games, specifically in Rio de Janeiro – based on interviews conducted two years after the Games as part of a broader ethnographic study. The positive connotations of legacy, even among these Olympic critics, places a straitjacket on conversation, leading activists to discuss specific legacy projects, at the expense of highlighting the very real harms of mega-event development, such as evictions, gentrification and militarization. As such, there is a need to deepen understanding that legacy encompasses all that is left behind after mega-events, not only the positive impacts.